Odpowiedź:
a) F=x , G= -6x+4
(F+G) x+(-6x+4)=x-6x+4= -5x+4
(F-G) x-(-6x+4)=x+6x-4=7x-4
d) F=2x-y, G= -(x-2y)
(F+G) 2x-y-(x-2y)=2x-y-x+2y=x+y
(F-G) 2x-y+(x-2y)=2x-y+x-2y=3x-3y
b) F=8 , G= -(4y+5)
(F+G) 8-(4y+5)=8-4y-5=3-4y
(F-G) 8+(4y+5)=8+4y+5=13+4y
e) F=-(206) , G= 20+b
(F+G) -(206)+20+b=-206+20+b=-186+b
(F-G) -(206)-(20+b)=-206-20-b= -226-b
c) F=a-4 , G=8-[tex]2^{2}[/tex]
(F+G) a-4+(8-[tex]2^{2}[/tex])=a-4+8-4=a
(F-G) a-4-(8-[tex]2^{2}[/tex])=a-4-8+4=a-8
f) F= -a-b , G= -(a+b)
(F+G) -a-b-(a+b)= -a-b-a-b= -2a-2b
(F-G) -a-b+(a+b)= -a-b+a+b=0
Szczegółowe wyjaśnienie: